An Ayurvedic Polyherbal Formulation Kaishore Guggulu: A Review - LATHER, AMIT (International Journal of Pharmaceutical & Biological Archive, 2011)
Kaishore guggulu is the one of the most famous Ayurvedic formulation that is used traditionally to support healthy joints, muscles and connective tissue. It is especially useful for balancing pitta in the musculoskeletal system (FDA). Kaishore guggulu is good in the treatment of and aggravated patients i.e. muscle pain. This review explains the pharmacological potential of Kaishore guggulu along with the other pharmacological activities of the part used of each ingredient in the formulation. This review helps the researcher to explode more about this important Ayurvedic formulation.